Psammomatous Arteriovenous Malformation-Brain: A Rare Histological Presentation Leading to Diagnostic Dilemma (Global Journal of Medical Research, 2014)
Occurrence of psammoma bodies (PB) in CNS is strongly associated with meningiomas. Its occurrence with arterio-venous malformation (AVM) is rare. We report a case of an unconscious 70 year old male who presented in the emergency department with mass lesion and on histop athology revealed a lesion composed of variable sized dilated and congested vascular channels which were mainly thin walled but with few thick walled vascular channels as well. Also noted were numerous lamellated calcified bodies (PB) which were present both intravascularly in small vascular channels as well as extra-vascular glial tissue. The minimal glial tissue included in the biopsy showed astrocytic prolife ration showing mild anisonucleosis and hyperc hromasia. Hence on light microscopy a differential diagnosis of Psammomatous cavernous haemangioma with a possibility of concurrent meningioma was suggested, as the synchronous presence of both the lesions is well documented in literature. A possibility of angiomatous variant of meningioma was also suggested.
Keywords: av malformation; cns; psamomma bodies